2013
DOI: 10.1016/j.jiph.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of infection control practices among intensive care nurses in a tertiary care hospital

Abstract: The infection control knowledge among the nurses was fairly good; however, there is still a wide scope of improvement with regular educational programs and in-house training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 31 publications
8
38
1
1
Order By: Relevance
“…However, they might lack the opportunity for MDRO education, as these guidelines have recently been issued. In contrast to the present study, the knowledge scores about MDRO in studies conducted in ICUs showed as high as a 77.2 to 84.4% correct answer rate (Shon & Park, ; Sodhi, Shrivastava, Arya, & Kumar, ). These higher rates may be because education for MDRO is focused primarily on the ICU, which carries a high risk of infection.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, they might lack the opportunity for MDRO education, as these guidelines have recently been issued. In contrast to the present study, the knowledge scores about MDRO in studies conducted in ICUs showed as high as a 77.2 to 84.4% correct answer rate (Shon & Park, ; Sodhi, Shrivastava, Arya, & Kumar, ). These higher rates may be because education for MDRO is focused primarily on the ICU, which carries a high risk of infection.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, availability of materials and equipment could affect compliance with IPC (Luo et al, 2010;Pereira et al, 2015). The result that providing sufficient resources and training improved handwashing from 66 to 97% (Helms, Dorval, Laurent, & Winter, 2010) (Shon & Park, 2016;Sodhi, Shrivastava, Arya, & Kumar, 2013). These higher rates may be because education for MDRO is focused primarily on the ICU, which carries a high risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that nursing students have attained a relatively modest level of perspective on training hospitals' infection prevention climate (M = 3.32, SD = 0.62). This result was in accordance with a study conducted in China , Ethiopia (Wami et al, 2016), and India (Sodhi et al, 2013). However, this result was lower than that conducted among nurses in Saudi Arabia (M = 3.86, SD = 0.51) (Colet et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The primary goal of the present study was to assess the knowledge and a tude of HCWs on IC and SPs. Studies have reported different levels of knowledge related to IC in HCWs, and the propor on of HCWs who were aware of 8,9 these prac ces ranged from 16-75%.…”
Section: Discussionmentioning
confidence: 99%